China catalyst : powering global growth by reaching the fastest growing consumer markets in the world - Holloman, Dave M., 1969- (Hoboken, New Jersey : Wiley, 2013)
Maximize your presence in the China market To drive the next round of global growth, companies will need to transition their operations and focus to one that serves the Chinese consumer. China Catalyst examines in-depth the transition currently underway in China from an export-led economic machine to a consumer-driven market. It outlines the economic imperative proving that greater consumer reach in China is a requirement in today's globally competitive market. China Catalyst also provides analysis that segments the market, helping you understand the hotbeds of em.
Targeting Demand Clusters and Expanding OutExpanding In; The Implications for Retailers and Manufacturers; IT as an Enabler; Notes; Chapter 10: The New Export Machine; Two Examples of China-Based Innovation: Kraft Foods and the Coca-Cola Company; Switching the Innovation Gear; Digital Culture; Multichannel Innovation; Notes; Chapter 11: The Path Forward; Challenges at a Crossroad; Final Thoughts on Strategy; Conclusion; Notes; About the Author; Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Investments, Foreign -- China; International business enterprises -- China; Economic development -- China; BUSINESS & ECONOMICS -- Exports & Imports; BUSINESS & ECONOMICS -- International -- General; BUSINESS & ECONOMICS -- International -- Marketing; POLITICAL SCIENCE -- International Relations -- Trade & Tariffs; Commerce; Economic development; International business enterprises; International economic relations; Investments, Foreign; China -- Commerce; China -- Foreign economic relations; China; Electronic books; Electronic books